Vivências de cuidadores de pessoas com distrofia muscular de Duchenne: um estudo fenomenológico - SILVA, Hidário Lima da (2024)
Introduction: Family caregivers of people with Duchenne Muscular Dystrophy experience the process of a family member affected by a rare, progressive, degenerative and disabling disease, and attribute meanings to it, according to their experiences and the social world in which they are inserted. Objective: To reveal the experiences of family caregivers of people with Duchenne Muscular Dystrophy. Methodological Course: This is a study with a qualitative approach, based on Alfred Schutz's Social Phenomenology. The study was carried out in the city of Imperatriz, Maranhão, Brazil, with participants being three mothers who played the role of caregivers for children with Duchenne Muscular Dystrophy. Data collection was carried out through in-depth interviews, in May 2023, using a semi-structured script, which contained questions concerning family composition and the process of caring for a family member with the disease. The study respected the ethical principles of research with human beings, being approved by the Research Ethics Committee, according to opinion number 6,329,518. Results: The statements were categorized into “reasons why”, referring to the past, and “reasons for”, to the future, considering the temporality of the phenomena experienced by the caregivers. From the experiences reported by the participants, three categories of analysis emerged, the first being: “The uncertainties of their children's diagnosis”, which portrays the experiences of mothers faced with the perceptions of abnormalities in their children's health, as well as the search for a diagnosis; “Diagnosis and care routine during treatment comings and goings”, in which the social worlds of mothers in relation to caring for their children are presented, such as comings and goings to health services, work overload, physical exhaustion and emotional responses of mothers facing the challenges posed by their children's illness; and finally, “Expectations for the future”, which portray the world-life of mothers guided by fears, uncertainties and the obscurity of good prognoses for their children, especially as they grow older. Final considerations: Mothers caring for a family member with Duchenne Muscular Dystrophy experience inherent aspects of the disease, related to their children, as well as experiencing situations that directly affect individuals, as people situated in a social world permeated by the process of caring for a sick child , sometimes with no prospects for good prognoses. It is necessary to understand these mothers as subjects in unique worlds and social realities, whose experiences and meanings are attributed in different contexts and are the result of subjectivities experienced in everyday life.